Erhöhte Sensitivität der Ganzkörperszintigraphie mit 131J für den Nachweis jodspeichernder Metastasen durch spätere Aufnahme-Zeitpunkte - Briele, B.; Hotze, A.; Grünwald, F.; Overbeck, B.; Biersack, H. J. (Nuklearmedizin - NuclearMedicine, 1990)
In the follow-up of thyroid cancer patients we sometimes observed discrepancies between elevated thyroglobulin levels and negative results of post- therapeutic or diagnostic scans 48 h and 72 h after oral application of131I routinely. Consequently, delayed 131I scans (96 h and later) were performed in addition. In all cases, delayed 131I scans either showed a higher imaging quality or additional metastatic lesions. Thus, posttherapeutic (and diagnostic) scans should include late images (4 d and later).